Negotiating Language Policy in Tourist Spaces: A Linguistic Landscape Study of Bilingual Warning Signs in Bali - Parthama, I Gusti Ngurah; Giri, Ni Luh Kade Yuliani; Setianingsih, Ni Ketut Alit Ida (Humanus, 2025)
The study investigates the bilingual warning signs found along Kuta and Legian beaches in Bali, Indonesia. It is within the framework of linguistic landscape (LL) analysis. The study aims to examine language policy—specifically the mandatory use of Indonesian language in public sign—interacts with the communicative needs of a globally diverse tourist population. Employing a qualitative research design, the study analyzed 33 bilingual signs through documentation and content analysis. It focuses on language positioning, institutional authorship, and semiotic features. Drawing on the theories of emplacement and indexicality by Scollon and Scollon (2003), the findings reveal a varied landscape. While some signs comply with national regulations by prioritizing Indonesian language, others, particularly those by private entities or tourism-sensitive authorities, prioritize English to accommodate international audiences. The study highlights the pragmatic tension between top-down language policies and bottom-up communicative practices in multilingual public spaces. It further illustrates that the visibility and hierarchy of languages on sign are influenced not only by legal frameworks, but also by spatial function and sociolinguistic context. These findings contribute to ongoing discussions in sociolinguistics, language policy, and semiotics. It shows bilingual public sign that serves as a site of negotiation between national identity and global communicability in tourism-driven environments.